CASE STUDY: EFFECTIVENESS OF DIABETES FOOT EXERCISES ON REDUCING BLOOD SUGAR LEVELS AND BLOOD PRESSURE IN DIABETES MELLITUS PATIENTS - Yuliandri, Dian; Lisum, Kristina (Yayasan Healing and Healthcare Education, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by persistent hyperglycemia and increased risk of complications such as peripheral neuropathy and vascular disorders. One of the effective and accessible non-pharmacological approaches in nursing practice is diabetic foot exercise. Objective: To determine the effectiveness of diabetic foot exercise in reducing blood glucose levels and blood pressure in type 2 DM patients with various comorbidities. This research employed a descriptive observational case study approach involving four patients diagnosed with type 2 DM and diverse comorbidities (pulmonary TB, COPD, neurological disorders, and diabetic foot wounds). The intervention consisted of a diabetic foot exercise program performed for three consecutive days, 10–15 minutes per session, using nine specific movements. Results: All patients demonstrated a significant reduction in blood glucose levels (80–200 mg/dL) and blood pressure stabilization within normal limits. Patients also reported improved sleep quality, reduced fatigue, and increased motivation and physical comfort. Diabetic foot exercise is proven to be an effective complementary nursing intervention for lowering blood glucose and blood pressure while improving the physiological and psychological status of type 2 DM patients, including those with limited mobility.